Application of EUCS and UTAUT Method to Analyze The Implementation of Donation-Based Crowdfunding System for Fundraising Mobile Applications - Mahesa Yahya, Lucky; Purwati, Sri; Patra Pertiwi, Triani; Hendra; Suradi, Agustinus (Jurnal Informasi dan Teknologi, 2023)
This research aims to determine the success of implementing the donation-based crowdfunding system in donation applications. This research will be carried out using a quantitative approach. Researchers will carry out observations and questionnaires using accidental sampling to ask respondents to answer questions that have been created in the form of a Google Form link. Researchers collected samples using the purposive sampling method. 100 people were used as respondents in this research. SmartPLS was used to carry out inferential data processing. In accordance with the results of the analysis discussion, it can be concluded that the variables in the UTAUT and EUCS models that are proven to have a positive and significant influence in measuring the level of success in implementing the donation-based crowdfunding system in applications are accuracy, content, facilitating conditions, performance expectancy, price value, social influence, user satisfaction, behavioral intention, and use behavior. Meanwhile, the effort expectancy and perceived credibility variables were proven to have no positive or significant effect in this research. Based on data analysis, the biggest variable that influences the level of success in implementing the donation-based crowdfunding system in applications is the behavioral intention variable towards use behavior. The second variable that has the most influence is performance expectancy on perceived credibility. Meanwhile, the other variable is user satisfaction with behavioral intention. From the results of the data processing that has been carried out, the variable that has the smallest influence on the level of success in implementing the donation-based crowdfunding system in the application is effort expectancy on behavioral intention. Next is the variable perceived credibility on behavioral intention.